(untitled) (Nigerian Journal of Pharmaceutical Research, 2020)
Background: Ciprofloxacin, a widely used antimicrobial agent, is available in Nigeria in various tablet and injectable dosage forms. In this era of fake and substandard drugs, it is important to be sure of the quality and antimicrobial potency of ciprofloxacin injectables imported and sold in Nigeria. Objectives: This study is aimed at evaluating and comparing the antibacterial efficacy of five different brands of ciprofloxacin infusion available in Nigeria against clinical bacterial isolates. Method: Ultraviolet-visible (UV-VIS) spectroscopy was used to determine the percentage content of active pharmaceutical ingredient in each brand, while antibacterial activities were compared against five bacterial strains including: Escherichia coli (E), Klebsiella pneumoniae (K), Pseudomonas aeruginosa (Ps), Proteus mirabilis (Pr), Staphylococcus aureus (St) and Salmonella typhi (Sa). Minimum inhibitory concentrations (MICs) and the minimum bactericidal concentration (MBCs) were determined by broth dilution method. Statistical analysis of the results obtained was done by ANOVA. Result: The percentage content of all the five brands of ciprofloxacin injection was not less than the specification (95-105%) of the British Pharmacopoeia, BP (2009). The susceptibility test showed that 16 out of 30 (53.3%) isolates were multidrug resistant. Ciprofloxacin was active on most of the clinical isolates which justify its wide use in treating infections in Nigeria; however, resistance to ciprofloxacin is increasing. Conclusion: Comparing the different brands, there was slight variation but no significant difference (p> 0.05) in their antibacterial activity (p= 0.96, 0.999 for sensitivity at 10µg/ml and MIC respectively).